Research on the Impact of Different Force Directions on the Mechanical Properties and Damage Evolution Law of Sandstone with Different Hole Diameters - Fukun Xiao; Renhe Li; Le Xing (Advances in Civil Engineering)
In this research, a uniaxial acoustic emission experiment was conducted on rock samples with different positions and diameters of the hole, and an analysis was made on the impact of different hole positions and diameters on the mechanical properties, failure, energy conversion, and acoustic emission-caused damage characteristics and laws of the rock samples. The results reveal as follows: first, due to the existence of holes in rocks, the stress-strain curve changes at each stage, accompanied by multiple stress drops. And the peak strength gradually reduces with the increase in hole diameter. At different hole positions, the duration that the rock sample passes through at each stage of the stress-strain curve varies, and the peak strength of the rock with the vertical hole is greater than that of the rock with the horizontal hole. This indicates that the bearing capacity and stability of the rock sample with the vertical hole are greater than those of the rock sample with the horizontal hole of the same diameter. Second, by making a comparison on the failure characteristics of rock samples, it is found that the intact rock shows brittle failure. For the rock sample with the horizontal hole, symmetrical tensile cracks initially appear in the upper and lower parts of the hole and finally form shear failure. As for the rock sample with the vertical hole, Y-shape failure originally presents and eventually forms N-shape failure with the increase in hole diameter. Over a comparison with the failure pattern of an intact rock sample, it is demonstrated that the final failure pattern and crack expansion trend on the rock sample vary with the change in the hole position and diameter. Third, as obtained by comparing and analyzing the energy conversion of the rock with different diameters of the hole, the energy conversion in the rock is changed due to the existence of holes, and the increase in hole diameter causes a gradual decrease in the elastic energy stored in the rock and gradual increase in the dissipated energy. And by comparing the energy conversion of the rock with different positions of the hole, it is acquired that the elastic energy conversion ratio of the rock with the vertical hole is higher than that of the rock with the horizontal hole. Furthermore, an explanation was made on the difference in the failure processes of the two types of rocks from the perspective of energy conversion.